Exploring team performance in endurance sports: how do individuals use their self-regulatory skills to perform optimally within a team? - Daphne H. Harmsen; Floor A. P. van den Brandt; Stein G. P. Menting; Florentina J. Hettinga; Marije T. Elferink-Gemser (Sport Sciences for Health, 2026)
Abstract Background Self-regulation is key to excelling in individual sports. However, little is known about the use of self-regulatory skills when athletes perform within teams ( group-based self-regulation ), where collaboration with teammates is required. Insight into an athlete’s success orientation, focusing on personal versus team success, might help understanding whether and how athletes adapt their self-regulatory skills in team events. Aims (1) Examine differences between individual and group-based self-regulation of endurance athletes within teams, stratified by success orientation. (2) Explore the relationship between behavior, satisfaction, and performance within teams. Methods Twenty-nine competitive long-track speed skaters (14 males, 15 females), aged 16 (15–16) years, skated an individual time trial (1500 m) and a team pursuit, consisting of skating three laps in a team of three skaters. Participants completed questionnaires on individual and group-based self-regulation, including the skills reflection, planning, evaluation, effort, self-efficacy, speaking up, coaching, and questions on general team behavior and satisfaction. Differences between individual and group-based self-regulation were tested with Two Related Samples Wilcoxon Signed-Rank test and the relationship between behavior, satisfaction, and performance were explored with Spearman’s rho correlations ( p